Pengetahuan dan sikap orang tua hubungannya dengan pola konsumsi dan status gizi anak autis - Maria Martiani; Elisabeth Siti Herini; Martalena Purba (Jurnal Gizi Klinik Indonesia, 2012)
Background: The prevalence of autistic spectrum disorder (ASD) has increased in recent years. In 1993 the prevalence of ASD was 2-4 cases per 10.000 children. The number increased significantly to 152 cases per 10.000 children in 2003 (0.15-0.2%). In addition to diet, nutritional status can be influenced by parent’s knowledge and attitudess toward children with autism. Improving parent’s knowledge and attitudess about autism can be an effective way to manage children with autism.Objective: To examine the relationship between parent’s knowledge and attitudes toward autism with dietary pattern and nutritional status of autistic children in SLBN Semarang.Methods: This was an observational study with cross sectional design. The subjects were students with autism who attended SLBN Semarang and their parents. A questionaire was used to collect the information on parent’s knowledge and attitudes toward autism, Food Frequency Questionnaire (FFQ) was used to obtain the data on gluten and casein consumption, whereas the data on nutritional status were measured by weight and height of the children. Chi square and Fisher Exact test were used to analyze the data.Result: As many as 55.3% of parents have good knowledge and 65.8% have a possitive attitudes toward autism. Fifty percent of children presented with good consumption pattern of gluten, 65% exhibited good consumption pattern of casein and 55.3% of autistic children had good consumption pattern of both gluten and casein. Almost half (47.4%) of the children were undernourished. There were no association found between parent’s knowledge and gluten and casein consumption (p>0.05); parent’s knowledge and nutritional status (p>0.05); and parent’s attitudes and nutritional status (p>0.05). Only parent’s attitudes towards autism was found to be associated with casein and gluten consumption pattern (p<0.05).Conclusion: There was a significant association between parent’s attitudes and consumption of gluten and casein in children with autism.